The Influence of Human Resource Management Certification and Work Motivation on The Performance of Human Resource Managers In Indonesia - Irwan Raharja (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2023)
The purpose of the current research is to analyze the influence of Human Resources (HR) management certification as well as work motivation toward the performance of HR managers in Indonesia. The current research uses a quantitative method by distributing a set of questionnaires to the participants. Data was collected from a group of human resource managers in Indonesia. The results were analyzed using simple linear regression analysis and multiple linear regression analysis using quantitative methods using AMOS software. The results show that the variable of HR management certification has a partial positive effect on motivation as indicated by the regression coefficient value of 0.412. The HR manager certification variable has a partial negative effect on the performance of human resource managers. This is shown by the regression coefficient value of -0.009. The work motivation variable for HR managers has a partial positive effect on the performance of human resource managers. The regression coefficient value of 0.349 shows those points. The HR manager certification variable as well as work motivation have a positive influence on the performance of HR managers. This effect is represented by a regression coefficient of 0.144. Thus, the implementation of the certification program must be well designed to improve the performance of HR managers. In addition, well-established plans can create a healthy environment that increases the incentives for HR managers to give their best performance.